The Effect of Organizational Learning and Innovation Climate on Innovative Work Behavior Mediated by Employees' Intrinsic Motivationwest Sumatra Province Regional Financial and Asset Management Agency - Muhammad Aliffarras Prasetyo; Elfiswandi Elfiswandi; Zefriyenni Zefriyenni (Sean Institute, 2026)
This study aims to examine the influence of organizational learning and innovation climate on innovative work behavior, mediated by intrinsic motivation among employees of the Regional Financial and Asset Management Agency (BPAM) in West Sumatra Province. Data collection was conducted through a survey and questionnaire distribution, with a sample of 93 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant effect of organizational learning on intrinsic motivation. There was a significant effect of innovation climate on intrinsic motivation. There was a significant effect of organizational learning on innovative work behavior. There was a significant effect of innovation climate on innovative work behavior. There was a significant effect of intrinsic motivation on innovative work behavior. Intrinsic motivation mediated the effect of organizational learning on innovative work behavior. Intrinsic motivation mediated the effect of innovation climate on innovative work behavior.